1998
DOI: 10.1002/(sici)1096-9101(1998)22:4<219::aid-lsm6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Treating bullous lung disease with holmium YAG laser in conjunction with fibrin glue and DEXON™ mesh

Abstract: Background and Objective Holmium YAG (Ho:YAG) laser energy is highly absorbed by water, and this property is useful to uniformly ablate pulmonary bullae. The current study summarizes the data of a 39‐month follow‐up of patients treated for bullae with a Ho:YAG laser. Study Design/Materials and Methods: We used a Ho:YAG laser from August 1994 to April 1997 to treat small pulmonary bullae in 50 patients. For the first five patients, Ho:YAG laser ablation was followed by resection for histological assessment. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, continuous exocrine pancreatic secretion from these small pancreatic ducts could lead to a pancreatic fistula after distal pancreatectomy, in spite of the use of fibrin glue. The combined use of fibrin glue and a polyglycolic acid mesh patch is a useful technique for the prevention of air leakage from the lung during thoracic surgery 11. This technique may also be useful for the prevention of pancreatic fistula.…”
Section: Fibrin‐glue Sealingmentioning
confidence: 99%
“…Therefore, continuous exocrine pancreatic secretion from these small pancreatic ducts could lead to a pancreatic fistula after distal pancreatectomy, in spite of the use of fibrin glue. The combined use of fibrin glue and a polyglycolic acid mesh patch is a useful technique for the prevention of air leakage from the lung during thoracic surgery 11. This technique may also be useful for the prevention of pancreatic fistula.…”
Section: Fibrin‐glue Sealingmentioning
confidence: 99%
“…Increased morbidity, particularly delayed pneumothorax, has been reported in patients treated with laser LVRS compared with staple LVRS [1]. Prior laser LVRS studies in animals have demonstrated that significant lung injury occurs in normal rabbit lungs with both CO 2 and Nd:YAG laser exposure, though the clinical and histologic presentations were distinct [8,10,11]. Holmium laser exposure is more efficacious but yields no differences in morbidity compared with Nd:YAG and CO 2 exposures [7].…”
Section: Commentmentioning
confidence: 99%